Comparison of Digisonde and CDSS measurement for the monitoring of the existence of the Ionospheric communication channel - Rejfek, Luboš; Mošna, Zbyšek; Beran, Ladislav; Chmelař, Pavel; Chmelařová, Natalija; Dobrovolný, Martin; Rozsíval, Pavel (Institute of Advanced Science Extension, 2016)
This paper describes systems for detection of the availability of the Ionospheric communication channel. The Digisonde and the Continuous Doppler Sounding System for the detection of the availability are used and are compared by means of here. Their precision, correctness and benefits of these systems are tested at the observatory Pruhonice in Czech Republic. The last part of this paper deals with ambiguities of both systems.
Porovnání kvality detekce existence ionosferického komunikačního kanálu pomocí CDSS a Digisondy
Keywords: CDSS; Digisonde; Ionosphere; Ionogram; Radio Link